PROCESS OF PROFESSIONAL ACTIVITY AND PREPARATION OF FUTURE TEACHERS OF PHYSICAL EDUCATION FOR THE IMPLEMENTATION OF VARIABLE MODULES (Physical Culture and Sport: Scientific Perspective, 2023)
The article highlights the problems of professional training of physical education specialists in the domestic scientific space and the normative and legal basis of professional training of future physical education teachers, defines the essence and structure of their readiness to implement variable modules.The developed scientific and methodological support for the training of future teachers of physical culture can be implemented in the practice of higher education institutions.The analysis of scientific sources made it possible to reveal the content of the basic concepts of the study and to characterize the preparation of future physical education teachers for the implementation of variable modules in the process of professional activity as a specially organized educational process in pedagogical universities aimed at obtaining a qualification that will allow to effectively perform professional tasks to harmonize the personality of students by means of physical culture and choreography in institutions of general secondary education.The preparation of future teachers of physical culture and choreography for the implementation of variable modules in the process of professional activity is considered as a specially organized educational process in universities aimed at obtaining a qualification that will allow to effectively perform professional tasks related to the harmonization of the personality of students by means of physical culture and choreography in institutions of general secondary education.It has been established that the need to reform the system of physical education of students on the basis of variability is recorded in regulatory documents.At the same time, the theoretical analysis of scientific research shows that the problem of training future specialists has not yet been sufficiently explored in pedagogical theory, and therefore has not been adequately reflected in the practical activities of educational institutions.
Keywords: variable modules; future physical culture teacher; professional training; physical culture; professional activity; essence and structure of readiness